Exegetical Views on Ismah of the Prophet Yusuf: A Re-Examination - Shittu, Abdulwahab Danladi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Qur’anic exegetes engaged one another in a serious debate over the disposition of Prophet Yusuf at the time of great temptation as captured in Qur’an 12:24. Against this background, this work exegetically studied the view of some scholars regarding the infallibility of Prophet Yusuf with a view to identifying the appropriate interpretation of the verse in question. Findings of the work revealed that while some scholars only considered the divine protection enjoyed by Prophet Yusuf in a narrow sense, others underscored the person of Yusuf as a Prophet of Allah and placed him above all human tendencies. Another group however, maintained the middle course between the two groups above. This paper concluded that Yusuf was a Prophet of Allah who enjoyed divine protection against committing sins and at the same time, he was a human being who could have an inclination towards evil thoughts without having a determination to commit sinful acts.